Motilitas Spermatozoa Ayam Kampung dalam Pengencer Air Kelapa, NaCl Fisiologis dan Air Kelapa-NaCl Fisiologis pada 25-29C - Triva Murtina Lubis (Agricultural Faculty, 2011)
Spermatozoa motility of local chicken in coconut water, physiological nacl and physiological nacl-coconut water at 25-29c)ABSTRACT. This study aimed to determine the effect of coconut water diluent, physiological NaCl and combination of coconut water-physiological NaCl to the survival of chicken spermatozoa at room temperature (25-29C). Semen was collected from a local chicken of 1.5 years old with weight of 2 kg in massage twice a week. Once evaluated, a good quality semen was divided into 3 treatment groups: coconut water (P1), physiological saline (P2), and its combination (P3) with the addition of 20% egg yolk [(P1) 80:0:20 (P2) 0:80:20 and (P3) 40:40:20] and stored at room temperature. Evaluation of spermatozoa motility conducted every 1 hour until reaching 40% of spermatozoa motility. Data obtained were analyzed using analysis of variance (ANOVA) with design patterns Split-plot and if there are differences between treatments tested by Duncan's multiple test. The results showed that motility of spermatozoa is significantly different (p 0.05) between storage time and diluent and there are interactions between storage time and diluent. P2 is able to maintain the minimum percentage of inseminated sperm motility (40%) for 4 hours, followed by P3 for 1 hour, and the lowest percentage motility of spermatozoa present in P1 for 0 hours. It can be concluded that the percentage of spermatozoa motility in group P2 is higher than P1 and P3.